If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 160 = -8(1 + -3p) 160 = (1 * -8 + -3p * -8) 160 = (-8 + 24p) Solving 160 = -8 + 24p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-24p' to each side of the equation. 160 + -24p = -8 + 24p + -24p Combine like terms: 24p + -24p = 0 160 + -24p = -8 + 0 160 + -24p = -8 Add '-160' to each side of the equation. 160 + -160 + -24p = -8 + -160 Combine like terms: 160 + -160 = 0 0 + -24p = -8 + -160 -24p = -8 + -160 Combine like terms: -8 + -160 = -168 -24p = -168 Divide each side by '-24'. p = 7 Simplifying p = 7
| 7(m-1)-6(m+5)=-37 | | (2x+3y-4z)-(x-y-z)= | | 6y+14=15-9y+14 | | 3(x-7)=8 | | -x-29=-13+2x | | x-9+x=3 | | -x-29=-12x-1 | | 4x^3+20x+10=0 | | y^2-14y=-36 | | 42x+50=1500 | | 2x^2+10x=-15 | | -10=4(x-5)+6x | | 2y+2(y-2)=7y-5(y-10) | | 2x^2+10x=15 | | 70=6x+5x-7 | | 4(-5-5x)=-200 | | 40+273= | | (2y+5)(3y+7)= | | 2(-5+x)=14 | | -8(x+1)+5(3x-4)=6(x-6)+14 | | 10ac*6ab*(-2bc)= | | 6(8+x)=6 | | 2x^2+3x=4 | | 14x+32=70 | | 6x-6-3x=-18 | | 6(-11+2n)-2n=-7(-n+3) | | 2(6+7x)=68 | | 0.75a+14=8 | | 5t-4=4+t | | 5(6x-10)=-20 | | (8a^2-6a-8)-(-6a^2+7a+5)= | | 4(n-6)-(2-3n)=6n |